Faktor-Faktor Yang Dipertimbangkan Konsumen Dalam Keputusan Menjadi Nasabah Pada PT. BPR PUSAKA Denpasar - Pramana, I Made Satria (E-Jurnal Manajemen, 2013)
Rural Bank or in Indonesia called Bank Perkreditan Rakyat (BPR) is one type of banking institutions that provide services to clients related to their activities. This study explains what factors are taken into consideration in the decision of consumers to clients in the PT. BPR Pusaka Denpasar. In this study using the 20 (twenty) variables and population in this study are all costumer of PT. BPR Pusaka Denpasar by respondents are taken as an example of as mani 100 people. The analysis technique used based on the method of factor analysis technique principal component (PCA) produced 5 (five) factor s that consumers. Consider in making the dicision to PT. BPR Pusaka Denpasar. Keywords : Marketing Strategy, consumer behavior, purchasing decisions